Updates in the pathogenesis of SJS/TEN - Joy Justice; Eric Mukherjee; Michelle Martin-Pozo; Elizabeth Phillips (Allergology International, 2025)
Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are severe cutaneous adverse reactions across a spectrum of severity characterized by widespread epidermal detachment and keratinocyte apoptosis. SJS/TEN develops due to a complex immunologic response after exposure to an associated drug antigen and/or its metabolite, and it results in significant morbidity and mortality. Complex immune mechanisms contribute to keratinocyte death. Drug-induced SJS/TEN has been shown to be strongly HLA class I restricted which has contributed to our understanding of mechanisms and has the potential to shape prevention and diagnosis. There is currently no evidence-based treatment outside of aggressive supportive care, and understanding the complete immunopathogenesis of SJS/TEN will be key for the development of efficacious and safe treatments that significantly reduce morbidity and mortality. This article focuses on what is new in the pathogenesis of SJS/TEN, including recent research on the mechanisms of T-cell activation, apoptotic and necroptotic mediators, other related molecules, genetic associations, and possible targeted treatment options.